Multi-skilling at a provincial training centre institution : post training evaluation - Florence, Taryn Merillia (Cape Peninsula University of Technology, 2012)
Thesis (MTech (Human Resource Management))--Cape Peninsula University of Technology, 2011 === As global and national markets become more competitive, businesses are forced to become more adaptable and the public service is by no means exempt from this phenomenon. Owing to a dynamic and ever-changing work environment, it is necessary for public servant employees to continuously update their knowledge and skills.